Innovative insights into engine performance and emissions - A numerical and experimental investigation of aliphatic hydrocarbons and renewable dimethyl ether - Wisam K. Hussam; Md Nurun Nabi; Mohammad G. Rasul; Ashfaque Ahmed Chowdhury; Fazlur Rashid; Nahina Islam (Case Studies in Thermal Engineering)
This study explores the performance and emissions characteristics of renewable dimethyl ether (DME) in comparison to three commonly used aliphatic hydrocarbons: diesel, decane, and dodecane. This research addresses a notable gap in the existing literature by integrating advanced numerical modelling with experimental validation to investigate the distinct combustion behaviours and emission profiles under various operational conditions. We employ a dual approach that integrates advanced numerical modelling using GT-Suite software with experimental validation. This research presents several innovative aspects, including a comprehensive comparative analysis of multiple fuels under varied engine operating conditions, the integration of advanced numerical modelling with experimental validation, the development of detailed performance maps for optimisation, and the provision of practical insights for future engine design and environmental compliance. The work has several phases, including the variation of engine speeds (800 rpm–2400 rpm) keeping other parameters constant, secondly, the variation of fuel injection timing (20° bTDC to 20° aTDC) and thirdly, the changing of compression ratio (12–28) for all four fuels. The study also includes the energy and exergy analysis for the same fuels. Our findings indicate that DME improves brake thermal efficiency (BTE for DME is 40.71 % higher than diesel (40.03 %), decane of 40.3 %, and dodecane of 40.18 %). Compared to diesel, NO emissions were reduced by around 34 %, 30 % and 29 %, using decane, dodecane, and DME, respectively. This presents a promising avenue for developing more environmentally friendly fuel alternatives in the future.